Legal Responsibility of Desk Collection in Threats of Psychic Violence Against Financial Technology Customers - Ja'far Shodiq; Muhammad Chusnul Khitam; Arianto Arianto; Nur Izzatul Khumairoh (Jurnal Independent, 2025)
Crime committed by desk collection is a type of crime carried out through electronic media that violates the Law on Electronic Information and Transactions (ITE Law), where in fact the debt collection process should be conducted ethically and politely towards debtors. However, the crimes committed by desk collection agents grossly violate both company procedures and the law. The crimes committed by desk collection agents, particularly in the form of psychological threats via online media through Financial Technology (Fintech) applications, constitute violations of the ITE Law, which prohibits intentionally and unlawfully sending electronic information containing threats or intimidation, which is punishable by law. The mistakes made by desk collection agents include carrying out collection methods such as insults, dissemination of debtor information that should be kept private, and repeated terror or intimidation, all of which violate the elements stipulated in the ITE Law. Based on the background above, the writer formulates the following research questions: First, how is the legal regulation regarding debt collection through electronic media? Second, how is legal protection provided for debtors who are victims of desk collection? The type of research used in this study is normative legal research, also known as library or doctrinal research. The legal materials used consist of primary and secondary legal materials, including: Article 29 in conjunction with Article 45B of Law Number 11 of 2008 on Electronic Information and Transactions, Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), which prohibits the use of personal data without the owner's consent. Protection for fintech customers is regulated in OJK Regulation No. 77/POJK.01/2016, which requires every fintech company to implement procedures and safeguards for the confidentiality of customer data, both personal and transactional